Effect of fermented feed on the growth performance, health condition and immune response of white leg shrimp Litopenaeus vannamei - Awad, MN; Khalafalla, MM; Khalil, RH; Abdella, BH; Mohamed, RA (Journal of the Hellenic Veterinary Medical Society, 2025)
The objective of this study was to evaluate the effects of rice bran fermented with commercial probiotic bacteria in relation to the culture density, with a focus on its impacts on the performance, health, microbiota, immune and transcriptomic responses of Litopenaeus vannamei as well as water quality. The white leg shrimp, L. vannamei (PL12) with an average weight of 0.34± 0.041 g was obtained from Egypt’s shrimp hatchery at Ghallioun project and cultivated in a stocking density of 150 and 200 animals/ m3. The shrimp were divided into three groups: three replicate each. Group I (G-I) was fed only on formulated feed (Control group), Group II (G-II) was fed on 50 % formulated feed and 50 % fermented feed and Group III (G-III) was fed on 100 % fermented feed. The results revealed that, the feed modification only considerably affected water temperature, but the stocking density significantly affected both the concentration of dissolved oxygen and the total ammonia nitrogen (P<0.05). The stocking density and feed fermentation had an impact on the individual / liter of the copepod presence in the culture bond. With 100% meal replacement, the maximum number of copepods was seen. High stocking density has resulted in a decrease in the number of copepods in the water. The phytoplankton decreased significantly as the food replacement increased. The highest growth performance was reported in shrimp larvae fed 100% formulated feed followed by 50% formulated feed and 50 % fermented feed then 100% fermented feed. The carbohydrate and the total ash percentage have increased while the crude protein content and fat content has decreased following the application of fermented feed. The application of fermented feed reduced the antioxidant capacity of L. vannamei while decreasing the expression of immune response genes and factors. In conclusion, using fermented feed may reduce the overall use of formulated feed and improve the health and immunity of shrimp larvae.